Evaluation of weight loss problem in weight sports according to athlete views - Civil, T.; Tekin, I.; Gündüz, N. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study is to evaluate the weight loss problem in weight sports according to the views of the athletes. The research is a qualitative study based on the opinions of the athletes. The research group consisted of elite fitness athletes (n = 40) composed of different branches. The open-ended questions used in the study were prepared by compiling the studies in the subject area and obtaining expert opinion. Interview questions consist of 2 parts in total. The first part consists of demographic information; the second part consists of a total of 5 open-ended questions: what the athlete does to reach the competition weight, rapid weight loss methods, methods used in recovery after weighing, effects of rapid weight loss on performance and advice to trainers. The purpose of the research was explained to the athletes participating in the study, and then they were asked to fill in open-ended questions in a comprehensive and descriptive manner. The research is a qualitative research based on athlete views. Descriptive analysis technique, one of the qualitative research methods, was used for the views of athletes in the analysis of the dataand 5 themes were determined. As a result of the research, the athletes stated that they pay attention to their eating and drinking in order to lose weight, increase the intensity of training, exercise sweat as a weight loss method by jogging and dressingin layers in sauna, consuming foods that give energy for recovery, take vitamin and mineral supplements, consume plenty of fluids, and that rapid weight loss affects their performance in an extremely negative way.